(untitled) (Advancements in Homeopathic Research, 2024)
Background: Type-2 Diabetes Mellitus (T2DM) is a chronic lifestyle disorder that calls for serious concern in today’s society due to its high morbidity and mortality rates and long-term detrimental effects on a number of body systems that can result in chronic complications if left unchecked or uncontrolled. The Homoeopathic system of medicine based on “Law of Similia” has shown its efficacy in treatment of T2DM as per various research studies. However, most of the studies in the past were done on Centesimal scale potency or mother tinctures, but there is lack of study on effectiveness of Fifty millesimal scale potency or comparative studies between both scales, in cases of T2DM. This randomized parallel arms study investigated the comparative effectiveness of a homoeopathic medicine given in Centesimal scale potencies versus Fifty millesimal scale potencies in a sample (n= 60) of patients suffering from T2DM